The Implementation of Inclusive Islamic Religious Education Learning In Schools - Hakim, Luqman; Fahmi, Muhammad; Muhid, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The presence of diverse religions, groups, and cultures in schools highlights the need for an inclusive Islamic learning model that actively instills values of tolerance. This study critically examines the implementation of Inclusive Islamic Religious Education (PAI) in two contrasting schools in Malang City: SMA Taman Harapan, characterized by interfaith diversity, and MAN 2 Malang, characterized by intra-Islamic diversity. Using a descriptive qualitative approach with a multiple-case study design, data were gathered through in-depth interviews, observations, and document analysis, and analyzed using the Miles, Huberman, and Saldana model. Results indicate that Islamic Religious Education teachers in both settings employ inclusive strategies—such as interactive dialogue, problem-based learning, contextual teaching, and project-based learning—that effectively foster mutual respect, enhance religious tolerance, and counteract radicalism among students. Ultimately, this research asserts that inclusive Islamic Religious Education is essential for strengthening tolerance and combating radicalism, presenting a viable model for humanistic and tolerant religious education in diverse school environments. The study substantially contributes empirical evidence by demonstrating the practical benefits of inclusive approaches in varying contexts, moving beyond normative claims to real-world educational impact.